The Contribution of Major Histocompatibility Complex Class II Genes to an Association with Autoimmune Diseases - Zakharova, M. Yu. (Acta Naturae, 2019)
Genetic studies of patients with autoimmune diseases have shown that one of the most important roles in the developing of these diseases is played by a cluster of genes of the major histocompatibility complex (MHC), as compared with other genome areas. Information on the specific contribution of MHC alleles, mostly MHC class II ones, to the genetic predisposition to autoimmune diseases is crucial for understanding their pathogenesis. This review dwells on the most relevant aspects of this problem: namely, the correlation between carriage of certain MHC II alleles and an increased (positively associated allele) or reduced (negatively associated allele) probability of developing the most common autoimmune diseases, such as type 1 diabetes, rheumatoid arthritis, multiple sclerosis, systemic lupus erythematosus, autoimmune thyroiditis, etc. The most universal haplotypes, DR3-DQ2 and DR4-DQ8, are positively associated with many of these diseases, while the universal allele HLA-DRB1*0701 is protective.